The Relationship on Knowledge of Women of Word About Contraception in Women with Participation Mother in Using it in Public Health Center Tanjung Morawa - Willhelmina Wahara (International Journal of Public Health Excellence (IJPHE), 2022)
The main problem faced by Indonesia in the field of population is population growth which is still high. Based on the Indonesian Demographic Health Survey (IDHS), the coverage of active family planning participants in Indonesia in 2012 was 76.39%. The purpose of this study was to determine the relationship between knowledge of couples of childbearing age about intrauterine devices with maternal participation in using them. This study uses an analytical survey design with a cross sectional approach. The population is the mother of couples of childbearing age as many as 6,052 people. Sampling using the slovin formula as many as 98 samples. Data processing using chi-square test . The results of the Chi -Square test results showed that the p value = 0.005 (< 0.05). The conclusion of this study is that there is a relationship between knowledge of fertile age couples about intrauterine contraceptive devices with participation in using them at the Tanjung Morawa Health Center in 2021 . It is hoped that this research can be input for health workers at the Tanjung Morawa Health Center to further improve health promotion regarding the use of intrauterine devices.